Non-targeted metabolomics reveals the taste variations during Baccaurea ramiflora Lour. fruit maturation - Yang, Chongcheng; Chen, Jiaqi; Zhang, Yang; Huang, Jianjian; Wang, Huachen; Chen, Jie (Frontiers in Plant Science, 2024)
Baccaurea ramiflora Lour. is a new kind of underutilized wild fruit tree; the metabolic reasons for its fruit flavor changes are not yet clear. In this study, the pink flesh of this excellent tasting fruit (BR) was used to reveal the metabolic causes of taste variations through five developmental stages. We identified 154 common differential metabolites of different developmental stages based on non-targeted metabolomics analysis. The accumulation of sugar and fatty acids increased significantly after 73 days, while citric acid decreased significantly. Flesh color accumulation mainly occurred 53 days ago, and vitamin accumulation occurred after 93 days. Interestingly, L-sorbose and 5-hydroxyindole-3-acetic acid were positively correlated with the sugar–acid ratio but negatively correlated with titratable acids. It indicated that L-sorbose and 5-hydroxyindole-3-acetic acid may be taste biomarkers of BR B. ramiflora. The results provided new metabolic lines of evidence for the taste variation during the ripening process of B. ramiflora.